An account of the genus Acrobolbus Nees (Marchantiophyta: Acrobolbaceae) in Thailand with a new record, Acrobolbus knightii (Mitt.) Briscoe - Sukkharak, Phiangphak (Phytotaxa, 2021)
Two species of Acrobolbus are recorded from Thailand. Of these, A. knightii is reported as a new to the country. A description, illustration, ecology, and geographical distribution of the species are provided.